HUBUNGAN PENGETAHUAN DENGAN TINDAKAN IBU TERHADAPTERJADINYA BIANG KERINGAT PADA BAYI 0-1 TAHUN DI DESA LAMA KECAMATAN HAMPARAN PERAK KABUPATEN DELI SERDANG TAHUN 2019 - Rismaida Saragih (Universitas Prima Indonesia, 2019)
Miliariasis often occurs in premature infants because the epidermal differentiation process and the ependix are incomplete. Cases of miliariasis occur in 40% - 50% of newborns. Appears at the age of the first 2-3 months, and will disappear by itself 3-4 weeks later. Sometimes these cases persist for some time, and can spread to the surrounding area. This study aims to describe the knowledge of the actions of mothers towards the occurrence of prickly heat in infants. This type of research is descriptive in nature which aims to determine the knowledge of the mother's actions against the occurrence of prickly heat in infants 0-1 years old in the old village of silver stretches of Deli Serdang Regency in 2019 using primary data and questionnaires using the total sampling method and population that is 30 people. Based on the results of research on the knowledge of the mother's actions against the occurrence of prickly heat in infants 0-1 years in the old village of silver expanse district of Deli Serdang Regency in 2019 the majority were knowledgeable as many as 13 people (43.3%), and the majority of respondents' actions were not carried out as many as 16 people ( 53, 3%). This is supported by the characteristics of the majority of people aged 20-25 years as many as 14 people (46.7%), the majority of junior high school graduates are 14 people (46.7%) and the majority of private employment is 13 people (43.3%). The conclusion of this research is knowledge with the mother's actions towards the occurrence of prickly heat in infants 0-1 years affects the duration of healing of milliariasis in infants, and this is influenced by education, age and low family income. Suggestions for mothers are expected for parents (mothers) to be more active in finding information about the occurrence of miliariasis in infants, carrying babies if miliariasis is not reduced.